Kinanthropometry IX - Olds, Tim; Stewart, Arthur; Marfell-Jones, Michael (Taylor and Francis, 2006)
This is an edited collection of peer-reviewed papers presented at the Ninth International Conference of the Society for the Advancement of Kinanthropometry. Defined as the relationship between human body structure and function, kinanthropometry is an area of growing interest, and these proceedings will be of use to students, academics and professionals in the areas of ergonomics, sports science, nutrition, health, and other allied fields. The assembled works represent the latest research findings across kinanthropometry, moving the discipline forward and promoting good practice and the exchange of expertise